The Effect of Various Plant Products on Mosquitoes Larvae Anopheles arabiensis and Culex quinquefasciatus (Diptera: Culicidae) - A. Kehail, Mutaman A.; Abdalla, Abdalla I. (Gezira Journal of Health Sciences, 2016)
This research aimed to study the larvicidal potentialities of three different local poisonous plants: ward elhameer N , ushar U and castor oil R (using different parts) leaves L , flowers F and seed S ) against two important species of mosquitoes ( Anopheles arabiensis and Culex quinquefasciatus ), by using two different methods of application (powder P and aqueous extract aq-ex). The standard methods of WHO for rearing and assessment of mosquitos’ susceptibility were carefully followed. The results revealed that, for Anopheles larvae, and according to the LD50 values, the products can be ranked from the more potent toward the least potent ones as follows:   RS , NL, UL , NF and lastly UF . The potentiality arrangement for Culex larvae are as follows: RS , UL , NL , NF and lastly UF